Intraoperative Sedation With Dexmedetomidine is Superior to Propofol for Elderly Patients Undergoing Hip Arthroplasty: A Prospective Randomized Controlled Study. Issue 9 (September 2018) - Mei, Bin; Meng, Gaige; Xu, Guanghong; Cheng, Xinqi; Chen, Shishou; Zhang, Ye; Zhang, Ming; Liu, Xuesheng; Gu, Erwei
Abstract : Background: Peripheral nerve block is a preferable method for elderly patients receiving hip arthroplasty. Sedation with dexmedetomidine may reduce postoperative delirium (POD). The aim of this study was to investigate whether intraoperative sedation with dexmedetomidine, as a supplementary to peripheral nerve block for elderly patients receiving total hip arthroplasty, can decrease the prevalence of POD. Methods: A prospective, randomized controlled study was conducted with patients 65 years of age or older who underwent total hip arthroplasty between June 2016 and June 2017. The patients were randomly assigned to receive a lumbosacral plexus plus T12 paravertebral block supplemented with propofol or dexmedetomidine for sedation. Incidence of POD was the primary endpoint and was determined with the confusion assessment method, and incidence of postoperative cognitive dysfunction (POCD) was assessed with the mini-mental state examination. The time of ambulation, discharge time, and complications over a 30-day postsurgery period were also recorded. Results: A total of 296 patients were randomly assigned to 2 groups. The patients sedated with dexmedetomidine had lower incidences of POD and POCD and were out of bed and discharged sooner than the patients sedated with propofol. There was no difference in complications between the 2 groups. Conclusions: As a supplementary to peripheral nerve block, intraoperative sedation with dexmedetomidine could be associated with a lower incidence of POD, which may have benefits on reducing the incidence of early POCD and offering a better short-term recovery for elderly patients receiving hip arthroplasty.